A lipomatous, cervicothoracic mass causing tracheal compression in a child - Michelle C. Moore; Lakir Patel; Rishi B. Parikh; Kimberly Lumpkins; Brian R. Englum (Elsevier, 2020)
Lipomatous lesions in children are significantly less common than in the adult population and tend to occur subcutaneously on the trunk or extremities. When they are found in the thorax, these lesions are more likely to be in the anterior mediastinum. Although pediatric lipomatous tumors are typically benign and slow-growing, mass effect can be seen in small spaces and malignancy remains a real threat. A 5-year-old male presented with an asymptomatic left neck mass, which was seen on imaging to extend from the visceral space of the neck into the posterior mediastinum to the level of the carina, causing tracheal deviation and compression. The mass was excised in its entirety and found to be a benign lipoma. Imaging is important to determine the exact location and interaction of the mass with cervical and mediastinal structures. Excision of the entire mass is the optimal treatment in order to make a definitive diagnosis, prevent complications from compression of mediastinal structures, and avoid recurrence.